A study of the equilibrium real exchange rate of the Maltese Lira - Central Bank of Malta (Central Bank of Malta, 2006)
This study provides the theoretical background and empirical investigation that are essential for the estimation of the equilibrium real exchange rate (ERER) for the Maltese lira.
Keywords: 330